Evaluation of Apical Extrusion during Conventional Retreatment with Three Endodontic Systems - Mircheska Marijana; Stojanovska Vera; Redzep Enis; Popovska Lidija (Balkan Stomatological Society, 2020)
Background/Aim: The aim of this study was to compare the apical extrusion during endodontic retreatment using three different endodontic systems.